Diurnal and semi-diurnal tidal structures due to O2, O3 and H2O heating - Vichare, Geeta; Rajaram, R. (My University, 2013)
Today with increased availability of data of middle atmospheric winds and temperature, modelling of middle atmospheric tides has acquired greater importance. The theory of atmospheric tides has two main parts: (i) Investigation of the sources of periodic excitation, and (ii) calculation of the atmospheric response to the excitation. Other than stratospheric ozone and tropospheric water vapour absorption, the thermal energy available from the absorption in Schumann–Runge (SR) continuum leading to photo-dissociation of O2 is important energy source for tides in the lower thermosphere. PHODIS radiative transfer model is capable of providing tidal forcing due to combined effect of solar and chemical heating in the wavelength region 116 to 850 nm. In this paper, we present an atmospheric tidal model based on classical tidal theory and the prime objective is to obtain the tidal structure due to conventional ozone and water vapour heating in conjunction with the O2 absorption. Mean wind and dissipation mechanisms are not considered. The present tidal model reveals that the diurnal amplitude peaks in mid to low latitudes, whereas semidiurnal component is stronger at higher latitudes. The semidiurnal tide is about an order of magnitude weaker than the diurnal tide. Also, semidiurnal wave has longer vertical wavelength than diurnal tide. The results of present model are qualitatively in good agreement with the other tidal models, which utilize more sophisticated parameterization. Thus, the salient features of the tidal structure are obtained using basic computations without considering the effects of background winds and dissipation processes. Further refinements to the model can serve as an inexpensive substitute to the presently available tidal models.
Keywords: Atmospheric tides; Atmospheric tidal model; Phodis heating; O2, O3 and H2O heating; Diurnal tide; Semi-diurnal tide